Political Dynasties and the Moderating Role of Good Public Governance - Dyah Setyaningrum; Hidayah Asfaro Saragih (Signifikan: Jurnal Ilmu Ekonomi, 2019)
The purpose of this study is to investigate the phenomena of political dynasties in Indonesia and its effect on local government performance. Moreover, this study also examines the moderating role of good public governance on the relationship between political dynasties and local government performance. Political dynasties define as the condition where local government head/vice head has a family connection with the head/vice head from the previous period or in other local government or with the legislative member. We use paired matched sample from local government in Indonesia during 2010-2015. The result shows that political dynasties negatively affect local government performance. Good public governance is proven to weaken the negative effect of political dynasties on the local government performance. Indonesia's central government need to regulate the practice of political dynasty as it is proved to decrease local government performance and encourage implementation of good public governance to reduce the adverse effects of political dynasties.